2007
DOI: 10.1007/s10194-007-0386-7
|View full text |Cite
|
Sign up to set email alerts
|

Rizatriptan vs. ibuprofen in migraine: a randomised placebo-controlled trial

Abstract: The objective of this study was to compare the efficacy of rizatriptan and ibuprofen in migraine. The study was a randomised placebo-controlled trial in a tertiary care teaching hospital. Migraine patients with <8 attacks/months were included. One hundred and fifty-five migraine patients were randomised to rizatriptan 10 mg (53), ibuprofen 400 mg (52) and placebo (50). Efficacy was assessed by headache relief, and headache freedom at 2 h and 24 h. Two-hour headache relief was noted in 73% in rizatriptan, 53.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
1
36
0
1
Order By: Relevance
“…[5][6][7][8][9] Migraineurs prefer treatment that includes a triptan over an analgesic alone. 10,11 The AAN recommends prophylactic therapy for patients whose migraines are frequent, severe, incompletely responsive to abortive therapy, or disabling.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Migraineurs prefer treatment that includes a triptan over an analgesic alone. 10,11 The AAN recommends prophylactic therapy for patients whose migraines are frequent, severe, incompletely responsive to abortive therapy, or disabling.…”
mentioning
confidence: 99%
“…Currently, triptans, which are agonists of 5HT 1B and 5HT 1D receptors, are the gold standard for migraine‐specific acute treatment 3 . Nonspecific analgesics such as acetaminophen (paracetamol) and nonsteroidal anti‐inflammatory drugs (NSAIDS) such as ibuprofen are also used to treat migraine attacks 4‐12 . Previous studies have suggested that combining a triptan with a nonspecific analgesic provides greater efficacy than either of the individual drugs administered alone 13‐16 …”
mentioning
confidence: 99%
“…In addition, among the 89.1% of patients who expressed a treatment preference, 69.9% preferred rizatriptan compared with 30% who preferred ergotamine/caffeine (p < 0.001) [29] . Misra et al have recently published data from a study of ∼ 50 patients per group, which compared rizatriptan with the NSAID ibuprofen or placebo [30] . In terms of efficacy, rizatriptan was superior to ibuprofen 400 mg and placebo for several measures, including headache relief (mild or no headache), improvement in functional disability and control of associated symptoms at 2 h post dose.…”
Section: Other Comparative Studies and Combination Therapymentioning
confidence: 98%
“…However, no significant differences were noted between rizatriptan and ibuprofen in terms of pain freedom at 2 h or sustained pain freedom at 24 h post dose. Although gastrointestinal side effects were observed more frequently in the ibuprofen group and palpitations were reported more frequently in the rizatriptan group, none of the patients discontinued the study for tolerability reasons [30] .…”
Section: Other Comparative Studies and Combination Therapymentioning
confidence: 99%